Granulomatous lung disease in a patient with a family history of hematological disorders - Overbeek, Maria; Van de Loosdrecht, Arjen; Vonk-Noordegraaf, Anton (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
A 29-year old patient presented with granulomatous lung disease and a family history of myelodysplastic syndrome/acute myeloid leukemia. She appeared to be a carrier of a mutation in the transcription factor GATA2. The case adds to the recent described heterogeneous clinical manifestations and syndromes in which, against a background of hematologic disorders, GATA2 mutations have been demonstrated, such as the Monomac and Emberger syndromes. In patients with a granulomatous disease and a history of (familial) hematologic disorders, the occurence of GATA2 mutations should be considered, as to gain further insight in the occurrence of granulomatous disease in a possible distinct phenotype among GATA2 mutation carriers.